2017
DOI: 10.5933/jkapd.2017.44.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microhardness of Bulk-base Composite Resins According to the Depth of Cure

Abstract: Composite resin becomes an essential material in pediatric dentistry. However, incremental filling of composite resin to minimize the polymerization shrinkage takes time. To reduce the polymerization shrinkage, clinicians and researchers have focused on bulk-filling materials. Bulk-base composite resin is newly introduced as bulk-filling composite resin. The purpose of this study was to evaluate microhardness profile of bulk-base composite resin according to the depth of cure. A high flow bulk-base material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…A direct method is to measure the amount of monomer, and one of the indirect methods is a comparison using microhardness 19,20) . Microhardness is a physical property that represents the characteristics of a material and represents the magnitude of the force that a material resists permanent deformation that occurs when an external force is applied to a minute part 21) . Therefore, in this study, Vickers Hardness Number was used to measure the physical properties of Bulk-Fill resin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct method is to measure the amount of monomer, and one of the indirect methods is a comparison using microhardness 19,20) . Microhardness is a physical property that represents the characteristics of a material and represents the magnitude of the force that a material resists permanent deformation that occurs when an external force is applied to a minute part 21) . Therefore, in this study, Vickers Hardness Number was used to measure the physical properties of Bulk-Fill resin.…”
Section: Discussionmentioning
confidence: 99%
“…In the study using the bulk-base resin, a significant difference in surface microhardness change was found from 4 mm in the case of the high flow bulk resin. In addition, it was reported that there was a significant change in surface microhardness between 0 mm and 2 mm of Medium Flow Bulk resin, but no significant change in surface microhardness was found between 2 mm and 3 mm, and 3 mm and 4 mm 21) . This…”
Section: )mentioning
confidence: 98%